Cyberbullying: risk factors for victimization in rural schools and the influence of school climate - Harrison-Pavlik, Ashley (Violence and victims, 2024)
This study evaluated the prevalence rates and risk factors for cyberbullying victimization and perpetration among 7th-12th grade students (n = 3,396) enrolled in 22 public school districts across Southern Illinois. Risk factors included victimization by traditional bullying, gender identity, cell phone use, and social media usage. We also examined perceptions of school climate and safety. We observed that traditional bullying victimization, gender identity, and social media usage predicted cyberbullying victimization. Similarly, perceptions of school climate and safety were significantly and positively correlated with cyberbullying victimization. In turn, perceptions of school climate and safety predicted cyberbullying perpetration. Rurality was a factor uniquely related to perpetration. Specifically, students from non-rural schools reported higher levels of cyberbullying perpetration than did students from rural schools. Our results underscore the need for intervention and prevention programs to focus on all forms of bullying and parental monitoring of social media accounts.